PHOTOBOOK DESIGN AS A PROMOTION MEDIA TO INTRODUCE WATERFALL TOURISM IN KARIMUN - Mangapul Siahaan; Jennifer Jennifer (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
Current technological advances can be applied in various fields, one of which is tourism. Furthermore, technology can make finding more extensive information about tourism in the country is easier. So that, they can plan before going on a trip. Looking at this aspect, technological developments are expected to help the tourism sector in Indonesia. This can be done by introducing one of the attractions in the area, namely Tanjung Balai Karimun. Which will be developed in a Photobook. Photobook is a type of book that is related to each other, which can be designed and laid out in advance. After that, it was printed and shaped into a book. This research aims to promote natural tourist attractions in the Karimun area. Because Karimun rarely has promoted tourism objects using photobooks. This research uses the R&D (research and development) method in designing photobooks. The result of this research is a photobook about waterfalls in Tanjung Balai Karimun which can introduce tourism